2017
DOI: 10.1007/s40843-017-9043-y
|View full text |Cite
|
Sign up to set email alerts
|

Directing nucleation and growth kinetics in solution-processed hybrid perovskite thin-films

Abstract: A heightened understanding of nucleation and growth mechanisms is paramount if effective solution processing of organic-inorganic perovskite thin-films for optoelectronic applications is to be achieved. Many fabrication techniques have been utilized previously to develop high-performance perovskite layers but there remains an absence of a unifying model that describes accurately the formation of these materials from solution. The present study provides a thorough analysis of nucleation and growth kinetics unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 45 publications
2
67
0
Order By: Relevance
“…In fact, perovskite thin films with millimeter‐scale crystalline grains have been reported by spin‐coating the hot precursor solution (70 °C) onto the heated substrates maintained at 190 °C (see Figure a,b) . The resulting thin films exhibit lower nucleation density at first glance, while further study revealed that the millimeter scale grains were also composed of polycrystalline microstructure with a grain size of <500 nm, instead of single‐crystalline domains as shown in Figure c 45a…”
Section: Controlling Precursor Solution Characteristics For Perovskitmentioning
confidence: 96%
See 2 more Smart Citations
“…In fact, perovskite thin films with millimeter‐scale crystalline grains have been reported by spin‐coating the hot precursor solution (70 °C) onto the heated substrates maintained at 190 °C (see Figure a,b) . The resulting thin films exhibit lower nucleation density at first glance, while further study revealed that the millimeter scale grains were also composed of polycrystalline microstructure with a grain size of <500 nm, instead of single‐crystalline domains as shown in Figure c 45a…”
Section: Controlling Precursor Solution Characteristics For Perovskitmentioning
confidence: 96%
“…Nonclassical growth theories, such as Volmer–Weber growth (island growth) behavior, Ostwald ripening, and oriented‐attachment45a have been used to try to describe the growth mechanism of perovskite crystals. Briefly, in Volmer–Weber growth, the precursor species favors mutual binding rather than binding to the substrate, the small clusters that do nucleate on the substrates surface form central nucleation sites, then islands initially coalesce from the pre‐existed nuclei until the growth is interrupted by a neighboring island.…”
Section: Controlling Precursor Solution Characteristics For Perovskitmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal growth kinetics are closely related to surface property of substrate, composition and concentration of precursors, additives, annealing temperature, and atmosphere condition [19][20][21][22]. Controlling the procedure of nucleation and growth during film deposition and annealing is a promising route to morphology management and device optimization [23,24]. For large-area preparation, it is generally difficult to obtain high-quality perovskite films, leading to moderate device efficiency.…”
Section: Fundamental Working Principles Of Perovskite Optoelectronic mentioning
confidence: 99%
“…The perovskite crystallization process consists of supersaturation, nucleation and crystal growth. When the film reaches supersaturation due to the evaporation of solvent, nuclei start to form and grow to bigger grains . The nucleation density or rate is critical to the grain size and morphology of perovskite films.…”
mentioning
confidence: 99%